Abacavir usage patterns and hypersensitivity reactions in the EuroSIDA cohort. Issue 4 (22nd December 2017) - Roen, A; Laut, K; Pelchen‐Matthews, A; Borodulina, E; Caldeira, L; Clarke, A; Clotet, B; d'Arminio Monforte, A; Fätkenheuer, G; Gatell Artigas, JM; Karpov, I; Kuznetsova, A; et al.
Abstract : Objectives: Five to eight per cent of HIV‐positive individuals initiating abacavir (ABC) experience potentially fatal hypersensitivity reactions (HSRs). We sought to describe the proportion of individuals initiating ABC and to describe the incidence and factors associated with HSR among those prescribed ABC. Methods: We calculated the proportion of EuroSIDA individuals receiving ABC‐based combination antiretroviral therapy (cART) among those receiving cART after 1 January 2009. Poisson regression was used to identify demographic, and current clinical and laboratory factors associated with ABC utilization and discontinuation. Results: Between 2009 and 2016, of 10 076 individuals receiving cART, 3472 (34%) had ever received ABC‐based cART. Temporal trends of ABC utilization were also heterogeneous, with 28% using ABC in 2009, dropping to 26% in 2010 and increasing to 31% in 2016, and varied across regions and over time. Poisson models showed lower ABC utilization in older individuals, and in those with higher CD4 cell counts, higher cART lines, and prior AIDS. Higher ABC utilization was associated with higher HIV RNA and poor renal function, and was more common in Central‐East and Eastern Europe and lowest during 2014. During 779 person‐years of follow‐up (PYFU) in 2139 individuals starting ABC after 1 January 2009, 113 discontinued ABC within 6 weeks of initiation for any reason [incidence rate (IR) 14.5 (95% confidence interval (CI) 12.1, 17.5) per 100 PYFU], 13 because of reported HSR [IR 0.3 (95% CI 0.1, 1.0) per 100 PYFU] and 35 because of reported HSR/any toxicity [IR 4.5 (95% CI 3.2, 6.3) per 100 PYFU]. There were no factors significantly associated with ABC discontinuation because of reported HSR/any toxicity. Conclusions: ABC remains commonly used across Europe and the incidence of discontinuation because of reported HSR was low in our study population.